NON-LITIGATION INHERITANCE DISPUTE RESOLUTION: A CASE STUDY OF MEDIATION BETWEEN A STEPMOTHER AND A STEPSON - Hidayat, Rahmat; Harahap, Mhd. Yadi; Siregar, Ramadhan Syahmedi (Journal Analytica Islamica, 2025)
Inheritance disputes are legally complex phenomena, not only due to the involvement of assets but also because they intertwine with emotional ties and cultural values within the family. In Indonesia, mediation as a form of out-of-court dispute resolution has become a preferred alternative to avoid open conflict, especially in inheritance cases involving sensitive family relations such as those between a stepmother and a stepson. This study aims to explore the dynamics of an inheritance dispute between a stepmother and a stepson following the death of the decedent, identify factors influencing the success of mediation, and evaluate the substantive fairness of the mediated agreement from the perspective of Islamic inheritance law. The methodology employed is empirical juridical research using a case study approach. Data were collected from official documents provided by the law firm handling the case, as well as relevant literature. The analysis was conducted using a qualitative descriptive method, with an emphasis on legal relevance and substantive justice. The findings indicate that the mediation process successfully produced a settlement between the stepmother and stepson regarding the distribution of inheritance. However, the novelty of this study lies in the discovery that the agreement deviated from the proportionality principles of Islamic inheritance law. While the mediation effectively prevented prolonged social conflict, the division of assets did not reflect the ideal distribution according to sharia principles. This highlights a critical gap in the enforcement of formal justice concerning inheritance rights, raising concerns about the substantive effectiveness of out-of-court mediation.